Descemet Membrane Endothelial Keratoplasty for Penetrating Keratoplasty - Al-Essa Aiad (Wolters Kluwer Medknow Publications, 2024)
BackgroundDescemet membrane endothelial keratoplasty (DMEK) has been utilized more frequently during recent years to treat penetrating keratoplasty (PKP) graft failures. The perioperative evaluation technique of anterior segment optical coherence tomography (AS-OCT) is increasingly significant. Our goal is to discuss DMEK surgical and clinical for subsequent PKP graft failure, along with significant surgical modifications and adjustments in accordance with preoperative assessment utilizing AS-OCT. Materials and MethodsPatients' records who performed DMEK for PKP failure were retrospectively reviewed. Demographic information, PKP graft size determined by postoperative problems, corneal donor endothelial cell density (ECD), AS-OCT, central pachymetry, visual acuity (VA) evaluated in Snellen units, intraoperative surgical procedure modifications, and postoperative ECD were all included in the data collection. ResultsThe observation was conducted with 16 patients with 16 eyes, nine males and seven females. The observation period is 18 months. DMEK was performed at an average age of 63. Preoperative AS-OCT was performed on all patients, and based on cases, surgical plans were created. Before processing DMEK, the mean VA is 0.04, and central pachymetry is 685 m. They improved considerably to 0.3 (P value = 0.001) and 542 m (P value = 0.008) at the most recent follow-up. About 93.75% of the grafts were adhered to after the procedure. Late decompensation caused a 6.25% graft failure rate. Graft detachment rates and cases requiring rebubble rates were respectively 18.75%. ConclusionIn DMEK for failed PKP, a good case-specific preoperative assessment by AS-OCT is essential. As a result, it relies on developing a surgical strategy that can improve surgical outcomes, lower the risk of complications, and quicken visual recovery.